Caspase-9 inhibition decreases expression of Mmp9 during chondrogenesis - Ramesova, A; Vesela, B; Svandova, E; Lesot, H; Matalova, E (Histochemistry and cell biology, 2022)
Besides cell death, caspase-9 participates in non-apoptotic events, including cell differentiation. To evaluate a possible impact on the expression of chondrogenic/osteogenic factors, a caspase-9 inhibitor was tested in vitro. For this purpose, mouse forelimb-derived micromass cultures, the most common chondrogenic in vitro model, were used. The following analyses were performed based on polymerase chain reaction (PCR) arrays and real-time PCR. The expression of several chondrogenesis-related genes was shown to be altered, some of which may impact chondrogenic differentiation (Bmp4, Bmp7, Sp7, Gli1), mineral deposition (Alp, Itgam) or the remodelling of the extracellular matrix (Col1a2, Mmp9) related to endochondral ossification. From the cluster of genes with altered expression, Mmp9 showed the most significant decrease in expression, of more than 50-fold. Additionally, we determined the possible impact of caspase-9 downregulation on the expression of other Mmp genes. A mild increase in Mmp14 was observed, but there was no change in the expression of other studied Mmp genes (-2, -3, -8, -10, -12, -13). Interestingly, inhibition of Mmp9 in micromasses led to decreased expression of some chondrogenic markers related to caspase-9. These samples also showed a decreased expression of caspase-9 itself, suggesting a bidirectional regulation of these two enzymes. These results indicate a specific impact of caspase-9 inhibition on the expression of Mmp9. The localisation of these two enzymes overlaps in resting, proliferative and pre-hypertrophic chondrocytes during in vivo development, which supports their multiple functions, either apoptotic or non-apoptotic. Notably, a coincidental expression pattern was identified in Pik3cg, a possible candidate for Mmp9 regulation.
Keywords: Caspase 9; buněčná diferenciace; inhibitory kaspas; Animals; Chondrocytes; chondrogeneze; Osteogenesis; osteogeneze; chondrocyty; kultivované buňky; Chondrogenic differentiation; Mice; Mmp-9; Non-apoptotic functions; Caspase-9; Cells, Cultured; Cell Differentiation; zvířata; Caspase Inhibitors; Chondrogenesis; kaspasa 9; Micromasses; myši